1998
DOI: 10.1002/(sici)1097-024x(199802)28:2<125::aid-spe146>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

An approach for decomposing N-ary data relationships

Abstract: SUMMARYOne of the most significant challenges in the use of entity relationship data models is in deciding whether to use a single relationship between several entities or a set of simpler relationships to represent a complex association. A practical eight-step approach is presented for analysis of n-ary relationships and decomposition into simpler relationships where appropriate. Relational database design concepts form the basis for this approach. An extended specification of cardinality constraints is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…N-ary associations can be easily expressed in terms of a set of binary ones plus additional constraints[24].…”
mentioning
confidence: 99%
“…N-ary associations can be easily expressed in terms of a set of binary ones plus additional constraints[24].…”
mentioning
confidence: 99%
“…McAllister et al (1998) [15] presented a practical eight-step approach for analysis of n-ary relationships and decomposition into simpler relationships wherever appropriate since one of the most significant challenges in the use of ER data models is in deciding whether to use a single relationship between several entities or a set of simpler relationships to represent a complex association based on the relational database design concepts. By using two examples for N:N:1 ternary relationship cardinality, they demonstrated that one relationship must remain as ternary and other relationship can be losslessly decomposed into two binary relationship.…”
Section: Cauadra Et Al (2010)mentioning
confidence: 99%
“…1 N-ary associations can be easily expressed in terms of a set of binary ones plus additional constraints [30]. 2 An association class could be represented as a regular class with n associations one for each participant plus a constraint restricting that no instance of the class can be related with the same exact set of participants.…”
Section: Structural Viewmentioning
confidence: 99%